2015
DOI: 10.1371/journal.pone.0143606
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effect of Aminothiol PrC-210 on Irradiated Inner Ear of Guinea Pig

Abstract: Radiotherapy of individuals suffering with head & neck or brain tumors subserve the risk of sensorineural hearing loss. Here, we evaluated the protective effect of Aminothiol PrC-210 (3-(methyl-amino)-2-((methylamino)methyl)propane-1-thiol) on the irradiated inner ear of guinea pigs. An intra-peritoneal or intra-tympanic dose of PrC-210 was administered prior to receiving a dose of gamma radiation (3000 cGy) to each ear. Auditory Brainstem Responses (ABRs) were recorded one week and two weeks after the radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In fact, dosimeters 2, 11 and 15 presented higher doses than dosimeters 12 and 13 due to their position next to the round cut-out. A few studies in literature have developed lead-shielding devices for preclinical assays involving small animals [5,[14][15]. Our results showed that the lead-based body-shielding device was able to attenuate close to 100% on the long axis of the conical tube, indicating a body equivalent dose below 1 Sv.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In fact, dosimeters 2, 11 and 15 presented higher doses than dosimeters 12 and 13 due to their position next to the round cut-out. A few studies in literature have developed lead-shielding devices for preclinical assays involving small animals [5,[14][15]. Our results showed that the lead-based body-shielding device was able to attenuate close to 100% on the long axis of the conical tube, indicating a body equivalent dose below 1 Sv.…”
Section: Resultsmentioning
confidence: 69%
“…However, local RT for small animals is not a simple task. Depending on radiation source, a physical barrier is necessary to deliver the dose in the target while sparing healthy tissues [5].…”
Section: Introductionmentioning
confidence: 99%
“…Should PrC-210 follow an entirely different clinical development path, with a clinical indication that has a clear short-term clinical end point, to establish human efficacy, such as suppression of radiotherapy-induced hearing loss (31)? And, once PrC-210 becomes an approved drug for this or another indication, then perhaps over a decade, should we explore PrC-210 as a diagnostic radiation radioprotector.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has a narrow preexposure time window and can only be administered via intravenous injection [ 14 ]. Moreover, it can induce side effects such as vomiting, hypotension, hypocalcemia, and allergic reactions [ 15 , 16 ]. Owing to these drawbacks, the clinical application of amifostine has been significantly limited.…”
Section: Introductionmentioning
confidence: 99%